2010
DOI: 10.1093/jae/ejp026
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Climate Change for Agricultural Sector Performance in Africa: Policy Challenges and Research Agenda

Abstract: The paper analyzed how climate change (CC) has shaped African agriculture in the past and how it might impact on African farm economies in the future and what adaptation strategies African farmers have adopted to cope with these changes. The analyses covered all key farming systems and agro-climates of Africa in 11 countries in which data was collected from over 10,000 farm household surveys. Results provided evidence that African agriculture and the welfare of its rural population are vulnerable to CC. The hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
62
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(69 citation statements)
references
References 27 publications
2
62
0
5
Order By: Relevance
“…changing crop varieties) on farm net revenues. At larger geographical scale (11 countries in Africa, with 10 000 farm household surveys) Hassan (2010) demonstrates that African agriculture and the related welfare are vulnerable to climate change, in particular for what concerns crop and livestock farming in dry lands, while Dono et al (2013) observed that the most important economic impacts are derived from yield instability. …”
Section: Results Of Modelingmentioning
confidence: 99%
“…changing crop varieties) on farm net revenues. At larger geographical scale (11 countries in Africa, with 10 000 farm household surveys) Hassan (2010) demonstrates that African agriculture and the related welfare are vulnerable to climate change, in particular for what concerns crop and livestock farming in dry lands, while Dono et al (2013) observed that the most important economic impacts are derived from yield instability. …”
Section: Results Of Modelingmentioning
confidence: 99%
“…S3) What kinds of public policy actions enable transformational shifts of cropping systems among large numbers of farmers? Large-scale empirical evidence on barriers to adaptation emphasizes the importance of tailored extension, information and financial services 13,22 .Shifts in staple crops will require transformation not only among farming communities but also along value chains and among consumers; a preparatory phase could usefully provide incentives for development of new processing and storage facilities, food and nutrition standards, consumer education and recipes, government procurement strategies, and piloting of markets for by-products. While policy options are myriad (e.g.…”
mentioning
confidence: 99%
“…refs. 13,[22][23][24][25] ), the key to the preparatory phase will be to create a flexible enabling environment for selfdirected change among farmers, consumers and value chain participants in response to climatic changes, situated within the wider context of rapid demographic and economic change 3,5,9 .This analysis, like many others, operates in a context of high uncertainty 9 . Our estimates of transformational adaptation are based on simulations of a single crop suitability model and are probably conservative owing to projected changes in climate extremes, pests and diseases, soil, trade and socio-economic constraints not considered here, and the fact that threshold exceedance may happen after 2100.…”
mentioning
confidence: 99%
“…The Zambezi River Basin in southern Africa provides a problem area suitable for this type of study both because of the hydrologic and agricultural importance for the people who live in the area (World Bank 2010;Hassan 2010;Collier et al 2008), i.e., the region is vulnerable to changes in climate, and due to previous studies concluding that the impact of climate change will likely be significant (Arora and Boer 2001;de Wit and Stankiewicz 2006;Lobell et al 2008;World Bank 2010). IPCC (2001) documents earlier work on the Zambezi, where these studies claim the basin will experience the greatest decrease in runoff as compared to the rest of Africa (e.g., Arnell 1999).…”
mentioning
confidence: 99%